2020
DOI: 10.1089/vio.2019.0025
|View full text |Cite
|
Sign up to set email alerts
|

Fear, Anxiety, and Expectation: Gender Differences in Openness to Future Gun Ownership

Abstract: There is extensive research on the correlates of gun ownership; however, less is known about the possible correlates of gun ownership among individuals who do not at present own firearms, but may be open to owning guns in the future. To that end, this study uses recently collected survey data from more than 900 nongun-owning U.S. adults to examine the factors associated with the likelihood of owning a gun in the future, motivations for prospective future ownership, and expectations about the perceived utility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 29 publications
2
28
0
Order By: Relevance
“…For example, Dowd-Arrow, Hill, and Burdette's (2019:2) recent analysis of national survey data showed that people who own guns tend to report lower levels of victimization fears and specific phobias than people who do not own guns. These patterns are clearly consistent with the protection motivation for gun ownership (Parker et al, 2017;Warner, 2020).…”
Section: Why Guns Should Promote Life Satisfactionsupporting
confidence: 78%
See 1 more Smart Citation
“…For example, Dowd-Arrow, Hill, and Burdette's (2019:2) recent analysis of national survey data showed that people who own guns tend to report lower levels of victimization fears and specific phobias than people who do not own guns. These patterns are clearly consistent with the protection motivation for gun ownership (Parker et al, 2017;Warner, 2020).…”
Section: Why Guns Should Promote Life Satisfactionsupporting
confidence: 78%
“…First, guns may help their owners to feel safe, secure, and protected (Buttrick, 2020;Celinska, 2007;Dowd-Arrow, Hill, and Burdette, 2019;Mencken and Froese, 2019;Shapiro et al, 1997;Taylor, 2013;Warner, 2020). The idea is that owning a gun can be reassuring to individuals as they cope with a world that they define as uncertain and dangerous.…”
Section: Why Guns Should Promote Life Satisfactionmentioning
confidence: 99%
“…For instance, challenges to one’s personal cultural worldview (Hirschberger, Pyszczynski, and Ein‐Dor 2009), and real (or perceived) social change (Britto 2013; Hirtenlehner and Farrall 2013; Jackson 2006) can lead to individual feelings of threat. As has been demonstrated within firearm research, threat‐based dynamics contribute both to increases in gun ownership (Steidley and Kosla 2018; Steidley and Trujillo 2020; Wright, Rossi, and Daly 1983) and more favorable attitudes toward guns (Warner 2020). Theories of risk perception argue that what people fear does not stem from individual cognitive assessments of personal threat to self/safety, but rather to socially shared worldviews (Rippl 2002)—the distal or diffuse anxieties, as discussed above.…”
Section: Introductionmentioning
confidence: 91%
“…As a case in point, Hauser and Kleck (2013) reviewed 16 studies on the effect of fear on gun ownership—only three found a significant positive effect and nine found no effect (see also Dowd‐Arrow, Hill, and Burdette 2019; Warner and Thrash 2020). Having actually experienced victimization appears to be a more consistent correlate of gun ownership and support for gun control (Filindra and Kaplan 2016; Hauser and Kleck 2013; Kleck et al 2011; but see Warner 2020; Warner and Thrash 2020). The lack of a clear association between such “proximate” fears and guns may be because, as Chadee and Ying (2013) note, rational calculations of crime risk are not tenable for individuals with little immediate experience with crime or victimization (e.g., residents of low crime areas, non‐victims).…”
Section: Introductionmentioning
confidence: 99%
“…Linking gender differences with economic and racialized status threat, Warner (2020) finds that non‐gun owning men are motivated by a constellation of cultural anxieties, such as concerns about (white) American identity and resistance to immigration, in their likelihood to consider owning a gun. Indeed, Stroud (2012) refers to contemporary patterns of gun appropriation as a form of “gendered racism,” finding in interviews with men who are gun carriers that “simply coming into contact with black men induces a desire to carry” (234).…”
Section: Introductionmentioning
confidence: 99%